Analysis of in situ bridge columns with exposed caisson foundations in a gravel stratum under lateral loading. Issue 3 (February 2020) - Chiou, Jiunn-Shyang; Tsai, Cheng-Chang
In this study, three in situ laterally loaded tests on bridge columns with caisson foundations in gravels were numerically explored. The three tests differed in the application position of lateral loads and the exposed length of the foundations. The analysis model used beam–column elements with distributed plastic hinges to simulate the column and a six-component Winkler beam model to simulate the foundation. The lateral stiffness of the foundation with combined moment and horizontal loading and a large exposed length was the smallest. Although the foundations were situated in a gravel stratum, the caisson with a large exposed length underwent significant foundation flexibility and nonlinearity; however, with increasing lateral loading, the influences of foundation flexibility and nonlinearity on the lateral displacement of the columns were reduced because column yielding limited the load transfer to the foundation. The horizontal soil reactions in front of the foundation and the side horizontal shear soil reactions along the caisson shaft provided major resistances to lateral loading (horizontal load and overturning moment). With increasing foundation exposure, the contribution of the base soil reactions increased, but the contribution of the side horizontal soil reactions decreased accordingly. The side vertical shear soil reactions and base normal soil reactions contributed moment resistance to reduce the foundation displacement and rotation and thus promoted the overall lateral capacity of the caisson foundations although they did not provide direct counterbalances to horizontal loads.